Group investigation integrated with socio-scientific issues: An experimental study on critical thinking and subjective well-being - Melysa Septiana; Ndzani Latifatur Rofi'ah; Erna Wijayanti (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Critical thinking and Subjective Well-Being (SWB) are important competencies in preparing students to face the demands of the Society 5.0 era. However, preliminary findings indicate that high school students' critical thinking and SWB skills are still relatively low. This study aims to analyze the effect of the Group Investigation (GI) integrated with Socio-Scientific Issues (SSI) on students' critical thinking and SWB. This study uses a quantitative approach with a Quasi-Experimental method with a Non-Equivalent Control Group Design. The sampling technique used purposive sampling, with class X1 as the experimental group and class X2 as the control group. The instruments used were a critical thinking test and a SWB questionnaire, and the data were analyzed using a significance test. The results showed a significant effect of the GI model integrated with SSI on students' critical thinking, with a significance value of 0.000 ≤ 0.05, and on students' SWB, with a significance value of 0.000 ≤ 0.05. These findings indicate that the SSI-based GI model is effective in improving critical thinking and SWB of grade X students. Recommendations provided include providing clear guidance, facilitating student product development, ensuring the accuracy of information sources during investigations, and conducting continuous evaluations so that learning objectives are achieved optimally.